Sifat Fisik serta Kandungan Bahan Kering dan Bahan Organik Silase Rumput Irian (Sorghum sp) yang Difermentasi Menggunakan lsi Rumen - Tanga, Ernika T.; Rumetor, SientJe D.; Rahardjo, Dwi D. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2006)
The aims of this experiment was to determine the physial characteristic, dry matter and organic matter content of Irian grass (Shorgum sp.) silage fermented with rumen content. The experiment was conducted at Laboratory of Animal Nutrition and Feed and Laboratory of Soil, Faculty of Agriculture Cenderawasih University during 2,5 months. Completely Randomized Design (CRD) consisted of 4 treatments and 5 replications was used in this experiment. For each treatment, two kg of Irian grass was supplemented with rumen content at level of 0, 2, 4 and 6%. Result showed that Irian grass suplemented with 4% of rumen contents were the best in quality of physical characteristic. The current study suggest that use of rumen content in Irian grass up to 6% after 28 days of ensiling had a good physical characteristics (i.e. texture, smell, color and pH) and dry mater and organic matter contents.